BICYCLISTS HELMET USE IN A FRENCH CITY. RESULTS FROM A FOLLOW-UP STUDY USING A SEMI-AUTOMATED VIDEO DETECTION SYSTEM. (7th October 2012) - Lagarde, E; Salmi, L-R; Messiah, A; Felonneau, M-L; Constant, A
Abstract : Background: While helmet use is likely to provide protection, their use remains rare in France and determinants are poorly understood. Aims/Objectives/Purpose: We aimed at assessing the impact of helmet provision on helmet use and at understanding facilitating factors and obstacles. Methods: Participants were non helmet users recruited at a bicycle loan facility in Bordeaux, France. After completing a questionnaire investigating their attitudes towards road safety and helmet use, participants were randomly assigned to three groups with the provision of 'helmet only', 'helmet and information' or 'information only', and to a fourth control group. Bikes were labelled with a colour code designed to enable observation of helmet use by participants while cycling, using a 7-spot semi-automatic video system located in the city. Results/Outcomes: A total of 1557 participants were included in the study. The likelihood of observed helmet use was significantly increased among participants of the 'helmet only' group (OR=7.73 (2.09 to 28.5)) but this impact faded within 6 months following the intervention. No effect of information delivery was found. The main factor leading to increased helmet use was peer pressure. Observed speed was not different between helmeted and non helmeted riders. Significance/Contribution to the Field: Providing a helmet will not be sufficient to achieve high rates of helmet wearing among adult cyclists in France. Integrated and repeated prevention programmes will be needed, including strategies to increase peer and parental pressure. The protecting effect of helmet is unlikely to be jeopardised by higher risky behaviours.